SCHOOL ENVIRONMENT AS A PROBLEM OF AGGRESSION AND VIOLENCE - Korchak, Leandra (The Modern Higher Education Review, 2017)
The phenomenon of violence and aggression, as well as the emergence of new forms of destructive influence on the functioning of Polish public life is understandable fear among the population. A particular problem for Pedagogical Sciences, Humanities and Law, the phenomenon of aggression and violence among young people, which affects the most important learning environment that is family, school and in general the environment surrounding the young man.